Trends of Pharmaceutical Design of Endophytes as Anti-infective - Tiwari, Pragya; Srivastava, Yashdeep; Bae, Hanhong (Current Topics in Medicinal Chemistry, 2021)
Plant-endophyte associations represent an inexhaustible source of novel metabolites, exhibiting significance in environment, agriculture and pharmaceutical perspectives. The global outbreak of life-threatening diseases necessitates a need for a more targeted approach through efficient drug-discovery programs. In recent times, endophytes as “bio-factories” have been extensively explored for the production of novel bioactive metabolites demonstrating therapeutic properties. Resources in computational biology co-integrated with combinational chemistry have made significant contributions in this field, aiding in discovery and screening of potential “drug-like” molecules from endophytes. The review provides a meta-analysis of bioactive metabolite production from endophytes, extensively discussing the bio-prospection of natural products for pharmaceutical applications. In light of emerging importance of endophytes as anti-infective agents, an exploration of the pharmaceutical design of novel chemical entities and analogues has enabled efficient and cost-effective drug discovery programs. However, bottlenecks in endophyte biology and research require a better understanding of endophyte dynamics and mechanism of bioactive metabolite production towards a sustainable drug discovery program.
Keywords: Pharmaceutical design